Intensité du travail et santé dans un organisme administratif : une enquête statistique à l’Agence nationale pour l’emploi - Anne-Françoise Molinié; Serge Volkoff (Perspectives Interdisciplinaires sur le Travail et la Santé)
A statistical survey on the occupational health of staff in the French National Employment Agency, ANPE (Agence Nationale pour l’Emploi) highlights certain effects of the intensity of work that characterizes jobs in the tertiary sector. The survey, conducted using a population of 2036 employees, involved 140 occupational doctors. Compared with the results of inter-professional surveys, these workers exhibit a fairly high prevalence of "minor" health disorders (joint pain, sleep disorders, feelings of edginess) and only an average prevalence of more serious disorders (sometimes accompanied by motor limitations, consumption of drugs or long periods of sick leave). Participants mentioned insufficient workspace and heavy time pressure, and commented on the "lack of distance" in their everyday work. However, the work is considered for the most part to be varied and useful to society. In this population, which is both motivated and vulnerable, links between work constraints (in particular those related to time and space) and health are obvious, but team work, sometimes training and often a keen interest in the job partially compensate for the discomfort it causes, although there is nothing to indicate whether these adjustments will continue to function in the long run.